The Role of Poetry in the Development of the Military Operations Era of Abbasid (132-232 H – 749-846 AD) - Amanj Salam Hamadameen; Mahdi Osman Husen; Hishyar Zaki Hasan (QALAAI ZANIST JOURNAL, 2024)
The research is dedicated to discussing the importance of poetry in the first age of the Abbasid Caliphate. Additionally, the research discusses the cultural exchange of the other nations with those of Arabs in Abbasid Caliphate and their contribution in the development of poetry and literature in that period. The research also discusses the role of the poets in the historical records in this period and the depiction of poetry in as crucial resource in writing history. The current research also discusses the well treatment of the poets by the Abbasid Caliphs and patronizing them which led to praising Caliphs by poets. The research found that poets were praising Caliphates and encouraged them to conquer Roman Empire, especially under the reigns of Harun al-Rashid and al-Muʿtaṣim biʾllāh. Further, the research found that poetry, in addition to historical records, could be considered as a reliable source to understand the situations in this period.